A Critical Review on Strategic Planning: Future of an Organization - Rangappa S. Ashi (Medical Research and Its Applications Vol. 4, 2024)
Planning is a continuous process, beginning with the setting of goals and objectives and then laying out a plan of action to accomplish them, put them into play, review the process and the outcomes, provide feedback to personnel and modify as needed. Strategic planning in nursing is concerned with what nursing should be doing. Its purpose is to improve the allocation of scarce resources, including time and money, and to manage the agency for performance. With strategic planning, the outlook becomes future oriented, resources are allocated systematically and rapid change is accommodated. Strategic Plans must be dynamic. Strategic plans are the blueprints that are to be updated as the environment changes.